Design, development and performance evaluation of tractor-drawn raised-bed pulse-planter for precision sowing of pigeonpea (Cajanus cajan) - KUMAR, RAJEEV; SAHOO, PRAMOD KUMAR; CHOUDHARY, ANIL K; INDRAMANI, INDRAMANI (The Indian Journal of Agricultural Sciences, 2020)
In order to promote pulse productivity in India, our government has given prime emphasis on farm mechanization in pulse farming so as to enhance their acreage and productivity under pulses. In this direction, IARI-New Delhi has developed a tractor-drawn ‘single-row/double-row raised-bed pulse-planter for pigeonpea (SR/DR-RB-PP)’ during 2014–2019. This pulse-planter consisted of inclined plate metering mechanism, chassis, power transmission system, raised-bed maker, etc. For designing of the cells in the incline plate of metering mechanism of planter, the physical properties of pigeonpea (Cajanus canja (L) Millsp) seeds were studied thoroughly. Bulk density, true density, 100-seed weight and sphericity of the pigeonpea seed ‘Var. Pusa–992’ were computed as 0.804±0.012 g/cc, 1.28±0.016 g/cc, 8.52±0.48 g and 0.81, respectively. Dimensions of chassis i.e. frame of planter were decided based on the mathematical calculations along with static simulation for stress analysis in ‘Creo-Simulation CAD 1.0 Designing Software’. Draft of developed pulse-planter was measured with 3-point dynamometer as 480±75 kgf. Recommended sowing travel speed, field capacity and field efficiency of tractor-drawn ‘SR/DR-RB-PP pulse-planter’ was 1.5–2.0 km/h, 0.2 ha/h and 83.8%, respectively. SR/DR-RB-PP planter worked satisfactory during field test. Developed pulse-planter was field tested, refined and validated at ICAR-IARI-Agronomy Research Farm, New Delhi during 2017–2019 for consecutive 3-years in Randomized Block Design (RBD) replicated 4-times for its agronomic performance compared with manual sowing of pigeonpea. On an average, the variation in grain yield under raised-bed double-row manual-sowing (RB–DR–MS) and raised-bed double-row pulse-planter sowing (RB-DR-PPS) was 1.18% while in raised-bed single-row manual-sowing (RB–SR–MS) and raised-bed single-row pulse-planter sowing (RB–SR–PPS), it was 2.43%. Grain, stover and biological yield followed the trend of RB-DR-MS>RB-DR-PPS>RB-SR-MS>RB-SR-PPS>FB-DR-MS>FB-SR-MS, respectively. Overall, RB–DR–PPS and RB–DR–MS were equally best performers w.r.t. grain and stover yield in pigeonpea. Thus, ‘SR/DR-RB-PP pulse-planter’ holds great promises in mechanization of pigeonpea sowing both in single-row and double-row raised-beds for improving the pigeonpea acreage and productivity coupled with time-saving and drudgery reduction so as to enhance farm productivity and farm incomes.